Stoma and tube stoma: two sides of the same coin? A scoping review - Alice Grandi; Ilaria Ester Midea; Letizia Toscano; Biagio Nicolosi (Infermieristica Journal)
Introduction: A stoma is a surgical opening in the abdomen that allows for the passage of feces and/or urine. It can be temporary or permanent, and the type of stoma depends on the affected section of the intestine or urinary tract. In neonates, a stoma may be necessary for various congenital or acquired pathologies. Stoma management in this age group requires specific skills and presents different challenges compared to adults. Aim: The aim of this review is to compare the advantages and disadvantages of stoma and tube stoma in neonates, to identify the clinical and care strategy that guarantees a better quality of life for the child and their family. Methods: A scoping review was conducted in the PubMed and CINAHL databases. The search included studies comparing the use of stoma and tube feeding in neonates with different pathologies. Results: Data analysis showed that: stomas offer immediate access to the intestine for feeding and decompression, but can be associated with complications such as retraction, ischemia, and peristomal dermatitis. Tube stoma allows for controlled tissue expansion of the intestine and better management of short bowel syndrome but requires more complex management and greater training of healthcare personnel. Conclusions: The choice between stoma and tube stoma in neonates should be individualized, considering the different clinical variables and the needs of the child and their family.